Auditoria em Saúde: justificativas de glosas no setor odontológico - Moimaz, Suzely Adas Saliba [UNESP]; Ayach, Carlos [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Saliba, Orlando [UNESP] (My University, 2012)
Objective – To collecting data about the main explanations for glosses and demonstrating the percentage of production loss in the odontologic procedures. Methods – It is about an epidemiological study of historical series, retrospective and quantitative, based on the data collection of DATASUS information system and reports realized by the city of Aquidauana/MS audit system from 2001 to 2010. Results – The results show that in this period, 921.300 odontologic procedures were presented as production; being 223.226 (24,2%) individual procedures and 698.074 (75,8%) collective. There were 23.881 (2,6%) glosses, being 10.158 (42,5%) in the collective procedures and 13.723 (57,5%) in the individual ones. The main cause for glosses related to individual procedures was the repetition of procedures for the same patient and the same tooth (42,4%). In the collective activities, it was the non-accomplishment of the oral health collective program (68,9%). There was an increase of loss in the individual procedures going from less than 5% in the period of 2001 to 2007; to 5,8 % in 2008; 8,9% in 2009 and 14,1 % in 2010 and in the collective procedures the loss reached 4% in 2010. Conclusion – It was concluded that the most frequent cause of glosses explanation was the repetition of procedures for the same patient and the same tooth in the individual cases and the non-accomplishment of the oral health collective program in the collective activities. The importance of the audit system as a trust-worthy instrument for the managers in the planning and evaluation of health actions with the intention of guarantee the solution of the serv-ices provided.

Objetivo – Fazer o levantamento das principais justificativas de glosas e o percentual de perdas de produção dos procedimentos odontoló- gicos. Métodos – É um estudo epidemiológico de série histórica, retrospectivo e quantitativo, baseado no levantamento dos dados do sistema de informação do DATASUS e relatórios do Sistema Municipal de Auditoria do município de Aquidauana-MS nos anos de 2001 a 2010. Resultados – Os resultados demonstram que foram apresentados 921.300 procedimentos odontológicos; sendo 223.226 (24,2%) procedimentos individuais e 698.074 (75,8%) coletivos. Ocorreram 23.881 glosas (2,6%), sendo 10.158 (42,5%) nos procedimentos coletivos e 13.723 (57,5%) nos individuais. A causa mais frequente de glosas referente aos procedimentos individuais foi a repetição de procedimento no mesmo paciente e no mesmo dente (42,4%). Nas atividades coletivas, foi a não realização do programa coletivo de saúde bucal (68,9%). Houve um aumento da perda dos procedimentos individuais passando de menos de 5% no período de 2001 a 2007; para 5,8% em 2008; 8,9% em 2009 e 14,1% em 2010 e nos procedimentos coletivos a perda atingiu 4% em 2010. Conclusão – Conclui-se que a causa mais frequente de justificativa de glosas foi a de repetição de procedimento no mesmo paciente e no mesmo dente nos procedimentos individuais e a não realização do programa preventivo de saúde bucal nas atividades coletivas. É importante o Sistema de Auditoria como um instrumento confiável aos gestores no planejamento e avaliação das ações de saúde.
Auditing in the service: glosses justification in the dental sector
Keywords: Dental audit; Unified Health System; Health services evaluation; Auditoria odontológica; Sistema Único de Saúde; Avaliação de serviços de saúde